Dinamika Kontrak ljarah dan Implikasinya Terhadap Pertumbuhan Bank Syariah: Analisis Laporan Keuangan 2020-2024 - Sari, Adelia; Erni; Citra Lestari, Bunga; Kafabillah, Zidnyfahma; Arsyad, Kamaruddin; Ahsan Kamil, Muh. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study analyzes the dynamics of ijarah contracts and their implications for the growth of Islamic banks in Indonesia, with a case study of Bank Syariah Indonesia (BSI) during the period 2020-2024. The ijarah contract is one of the main financing instruments in Islamic banking that provides an alternative to leasing the benefits of assets without transferring ownership. Using a qualitative, normative legal approach and financial statement analysis, this study finds that ijarah-based financing, especially ljarah Muntahiyah Bit Tamlik (IMBT), shows a significant increase in the productive assets of Islamic banks. The value of ijarah assets increased from IDR 1.5 trillion (2020) to IDR 3.1 trillion (2024), reflecting the strategic role of this contract in driving the growth of Islamic financing. Despite facing challenges such as limited public understanding and operational complexity, the ijarah contract remains relevant and has the potential to expand Islamic financial inclusion. This study contributes to the understanding of the effectiveness of the ijarah contract as a driver of Islamic bank growth and highlights the need for increased education and strengthened regulations.